Student Engagement in Learning : The Impact of Depression, Self-Efficacy, Resource Management, Emotional and Cognitive Factors - Najwakhida, Ellysa; Aeni, Ida Nur (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the influence of depression, self-efficacy, resource management, and emotional and cognitive factors on student learning engagement. This study uses a quantitative approach, with data collection techniques in the form of questionnaires. Respondents of this study were 171 high school students who were determined by the Convenience Sampling technique. The data analysis technique used is a multiple linear test using SPSS by conducting prerequisite tests consisting of normality test, linearity test, multicollinearity test, and heteroscedasticity test. The results of this study indicate that depression, self-efficacy, resource management, emotional factors, and cognitive factors significantly affect student learning engagement. However, emotional and cognitive factors partially do not affect learning engagement. The implications of this study are the importance of knowing students' mental health, developing self-efficacy and resource management skills, strengthening students' emotional and cognitive factors, and implementing programs that must be implemented in every school to improve student learning engagement.